Effects of Er,Cr:YSGG and Diode Lasers on Clinical Parameters and Gingival Crevicular Fluid IL-1β and IL-37 Levels in Generalized Aggressive Periodontitis - Ahmet Cemil Talmac; Metin Calisir; Emre Gurkan Eroglu; Abdullah Seckin Ertugrul (Hindawi Limited, 2019)
Aim. The objective of the current study is to analyze the correlation between cytokine levels and periodontal parameters in aggressive periodontitis patients before and after periodontal treatment that was performed by using two different laser therapies. Materials and Methods. Twenty-six generalized aggressive periodontitis patients were treated with three different methods (SRP, SRP+diode laser, and SRP+Er,Cr:YSGG laser) applied to three different half-jaws in the same patients. Pre- and posttreatment clinical periodontal parameters and GCF IL-1β and IL-37 levels were measured. Results. There was a statistically significant decrease (p<0.05) between pretreatment and posttreatment clinical periodontal parameters and IL-1β and IL-37 levels. When the reduction rates of IL-37 and IL-1β levels after treatment were evaluated, the decrease in IL-37 and IL-1β levels after treatment was lowest in the SRP group and highest in the SRP+Er,Cr:YSGG group. In addition, the amount of decrease in IL-1β in SRP+diode and SRP+Er,Cr:YSGG groups was found to be higher than that in IL-37. Furthermore, there was a positive correlation between IL-37 and IL-1β in all groups (p<0.01). Conclusion. Er,Cr:YSGG laser is more effective than diode laser for the treatment of aggressive periodontitis. IL-37 and IL-1β are cytokines that function together and thus must be evaluated together.